Determinants of Foreign Direct Investment Outflow of Malaysia : Vector Error Correction Model - Yong, Jhen Kai; Jerome, Kueh; Yong, Sze Wei; Yau, Josephine Tan Hwang; Audrey, Liwan (Human Resource Management Academic Research Society (HRMARS), 2019)
This study aims to investigate the determinants of outwards FDI of Malaysia. This study adopted annually data of outwards FDI, market size, trade openness, technology level, and exchange rates which ranging from 1986 to 2016. Augmented Dickey-Fuller (ADF) unit root test, Johansen and Juselius cointegration test and Vector Error Correction Model (VECM) are employed to determine the relationship between the outward FDI and its determinants. The results of unit root tests show that all the variables were stationary after first difference, I(1). Besides that, the cointegration results imply a stable long run equilibrium exist between variables. Based on VECM results, the outwards FDI is affected by all the explanatory variables in both short run and long run. The results obtained are beneficial for the government and policy makers to implement and enhance the outwards FDI in Malaysia.